2017
DOI: 10.3233/cbm-170286
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of SNHG1 suppresses cell proliferation and invasion by regulating Notch signaling pathway in esophageal squamous cell cancer

Abstract: These results indicated that lncRNA SNHG1 may be a potential predictor of prognosis in ESCC patients and a novel target for ESCC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 21 publications
2
55
0
Order By: Relevance
“…The results from Yan et al found that SNHG1 was significantly up-regulated in esophageal carcinoma tissues [36]. Zhang et al obtained similar results for SNHG1 in esophageal squamous cell cancer [37]. miR-195 was also proven to be a tumor suppressor in several cancers.…”
Section: Hepg2 Huh7mentioning
confidence: 84%
“…The results from Yan et al found that SNHG1 was significantly up-regulated in esophageal carcinoma tissues [36]. Zhang et al obtained similar results for SNHG1 in esophageal squamous cell cancer [37]. miR-195 was also proven to be a tumor suppressor in several cancers.…”
Section: Hepg2 Huh7mentioning
confidence: 84%
“…Studies have shown that some snoRNAs play important roles in biological processes, and dysfunction of snoRNAs may lead to oncogenesis [16]. It has also been reported that snoRNAs could serve as biomarkers in several diseases, including cancers [23].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA SNHG1 may be a potential predictor of prognosis in ESCC patients and a novel target for ESCC treatment [16].…”
Section: Introductionmentioning
confidence: 99%
“…With the advances in high throughput sequencing, an increasing number of snoRNAs have been screened and are emerging as important RNAs, thereby attracting the attention of researchers. Studies have shown that some snoRNAs play important roles in biological processes, and dysfunction of snoRNAs may lead to oncogenesis [16]. It has also been reported that snoRNAs could serve as biomarkers in several diseases, including cancers [23].…”
Section: Discussionmentioning
confidence: 99%
“…SNHG8 may play oncogenic roles in the malignancy of ESCC, and offer potential biomarkers for the diagnosis and prognosis of ESCC [15]. LncRNA SNHG1 may be a potential predictor of prognosis in ESCC patients and a novel target for ESCC treatment [16].…”
Section: Introductionmentioning
confidence: 99%